Fabricated Hadith as an Epistemic Threat: A Literature Review on Its Origins, Characteristics, and Social Mitigation - Ichsan Kamil; Zainal Arif; Alhafidh Nasution; Abdul Wahid (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
This article addresses the critical issue of maudhu’ (fabricated) hadith as a significant challenge in the study of ‘ulum al-hadith, given its direct impact on the authenticity of Islamic teachings as derived from the Qur’an. It aims to provide a comprehensive explanation of the concept of maudhu’ hadith, covering its definition, historical emergence, driving factors, characteristic indicators in both sanad (chain of transmission) and matan (text), the jurisprudential rulings on its narration and practice, as well as the socio-religious consequences it engenders. Utilizing a literature review methodology, the study critically examines relevant books, articles, and scholarly works. The findings demonstrate that Maudhu’s hadith are narrations falsely ascribed to the Prophet Muhammad (peace be upon him), rendering them unacceptable as evidence and prohibited from transmission except for the purpose of exposing their falsehood. The emergence of these fabricated hadith is influenced by diverse motives such as political conflict, adversarial strategies against Islam, ignorance, sectarian fanaticism, ethnic primordialism, and personality cults. Their dissemination creates serious problems by deepening community divisions, distorting perceptions of Islam, diminishing the prophetic image, and weakening religious motivation. Furthermore, the article emphasizes the crucial role of ulama strategies, including transmitter criticism, sanad verification, narrative comparison, the establishment of critical principles, and the codification of fabricated hadith, as essential measures to safeguard the purity of the Sunnah.